ANALISIS PERBUATAN MELAWAN HUKUM PEMBANTU PERUSAHAAN DI KOTA MAKASSAR: ANALYSIS OF AGAINST LEGAL ACTIONS OF COMPANY HELP IN MAKASSAR CITY - S. Mansyur, Imam; Almusawir; Tira, Andi (Faculty Of Law Bosowa University, 2022)
This study aims to: (1) determine the elements of unlawful acts on the sale of company goods to third parties in Makassar. (2) knowing the legal remedies taken by the company against the helper selling the company's goods without permission to a third party. The type of research used is normative-empirical, normative research is used to answer the first problem, and empirical research is used to answer the second problem. The results of this study indicate that: (1) the sale of company goods by assistants to third parties without the company's permission is an act against the law as regulated in Article 1365 of the Civil Code. (2) Legal efforts made by the company against the company's assistants filed a lawsuit to the Makassar District Court.